A research on the compensation and benefit in Telekom Malaysia (TM) / Marliza Muhammad Rosli - Muhammad Rosli, Marliza (Faculty of Business and Management, 2009)
Compensation is the Human Resource Management function that deals with every type of reward individuals receive in exchange for performing organizational tasks. Employee benefits which included mandatory benefits and fringe benefits are becoming essential portion of the compensation packages that are offered by organizations to their employees. The purpose of this study was to reveal whether the employee in TM are satisfied with the compensation and benefits that offered by TM to its employee and whether the compensation and benefits that offered by TM are sufficient to its employees. The result of the study suggested that more offer in compensation and benefits that offered by the organization will make more loyalty among the workers. There are many type of compensation and benefits that offered by the organisation to its employees such as allowance, promotion, bonuses, loan and so on. The further result is all type of compensation and benefits in the organization are sufficient to its employees except medical benefit. The organisation should more care in medical benefit among the Non-Executive to make more loyalty workers in the organization and should appreciate their worker that was help the organization in achieve the goal of business. The organization should care its employee from resign and working with the competitor or other company.